Gambaran Karakteristik Pasien Erupsi Obat Alergi di RSUD Arifin Achmad Pekanbaru Periode 2010 – 2014 - Endang H Darmani; T.Sy. Dessi Indah S As; Yuni Eka Anggraini; Olivia Makmur (Jurnal Ilmu Kedokteran, 2016)
Allergic drug eruptions is one of most dermatology cases can find in Arifin Achmad General Hospital Pekanbaru forlast four years and study about the characteristic description of allergic drug eruption’s patients never been describedbefore. To describe the characteristic of allergic drug eruption’s patients in Arifin Achmad General Hospital PekanbaruIndonesia. This is a descriptive retrospective study with 35 subjects, which is describing the most common type ofmorphologic skin eruption, groups of gender and age were affected , and etiology drugs were suspected. Mostcommon type of morphologic skin eruption is exfoliative dermatitis (eritroderma) (42,8%), most frequently genderaffected is women (60%) and group of age most frequenly affected is 41-50 (25.7%) years old. Antibiotics is the mostcauses were suspected (60%). Exfoliative dermatitis, women and age 41-50 years old were most common characteristicdescription of allergic drug eruption’s patients in Arifin Achmad general Hospital Pekanbaru time periode 2010-2014.